Analisis Pengaruh Pemberian Latihan Two Step Ladder Drill Terhadap Agility Dan Speed - Ilham Samudra Kusuma; Anna Noordia (Journal Innovation In Education, 2024)
In futsal, players are required to always move quickly and control the ball in order to increase their chances of scoring goals in the opponent's goal. This requires good physical condition, especially in the components of endurance, strength, speed, agility, flexibility and coordination. However, according to the results of observations and observations of athletes in the 12 year old birth category at the Gresik Futsal School, they showed weaknesses in their physical condition, especially in agility and speed. So this research aims to analyze the effect of providing two step ladder drill training on agility and speed in 12 year old athletes at the Gresik Futsal School. This research is a quantitative research with an experimental approach involving 14 samples. Data collection was carried out using the pretest and posttest method, then a statistical test was carried out in the form of a paired T test. Through this statistical test, for both agility and speed, a p-value of 0.000 was obtained. Thus, it can be concluded that there is a significant effect of providing two step ladder drill training on increasing agility and speed in Gresik Futsal School athletes born aged 12 years.